E-LEARNING KONIMEX - , DIKA HENDRAS PRATIWI, Muhammad Fakhurrifqi S.Kom., M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT. Konimex Solo is one of the largest pharmaceutical and food products in Indonesia, which has employees from all over Indonesia. PT. Konimex have a desire to provide a place to learn the employee. The place is a place of learning is electronic learning , which is now better known as e-learning. Technology in Indonesia in the era now can be regarded as the basic needs of society, which means that the technology is no longer an expensive thing that can only be accessed by certain circles. Basic needs of this technology will want to be used by PT. Konimex for employees with e -learning has on the company. E-Learning Konimex is used to provide material and where to measure employees' understanding of the material that has been provided. The material provided is of type PDF. E-Learning Konimex also a test page for pemahan employees know about the materials separately, ie the page multiple choice exam and essay exams . Page discussion forum is also provided in the system , with the aim of helping employees communicate with other employees or employees with head divis . The results of the research and testing of the system, demonstrate elearning is an effective Konimex as a place to convey the material to employees , in addition to reading material that has been provided, the employee can also download the material via the download link material. Results of multiple-choice exams can be immediately seen after the employee completed work on the problems , while the results of the essay test scores, can be seen after the employee admins correcting answers and upload grades essays . There is a printed report as evidence of the value of employee capabilities . Communication between employees and heads of divisions in the forums by making a comment on the status and status .